Vaccination recommended for pregnant women - Justyna Magdalena Skolarczyk; Dawid Dominik Łabądź; Joanna Pekar; Barbara Nieradko-Iwanicka (Kazimierz Wielki University, 2017)
A vaccine is a formulation of biological origin that contains substances capable of inducing immune processes without the ability to cause a disease. Vaccination is considered the best mean to prevent infectious diseases and their serious complications. Vaccination of a pregnant women can provide protection against severe infectious diseases of both pregnant women and their children. The aim of the study is to present currently available types of vaccines recommended for pregnant women and indications for their use by analyzing the data available in the PubMed, and Medline electronic databases. In the United States, vaccination recommendations for pregnant women include inactivated influenza vaccine and tetanus and diphtheria toxoid vaccine (Tdap). In some countries, pregnant women also receive a vaccine against hepatitis B as well as anti hepatitis A and E. There are also studies on vaccines against the RSV virus and pneumococci. Vaccination is the most effective form of prevention of infectious diseases and their use during pregnancy does not entail any additional risk to the mother or her baby. The benefits of vaccination are huge, so pregnant women should take  recommended vaccination and shouldn't  be afraid of using them.